PUBLIC RELATIONS PROGRAM MANAGEMENT AT MADRASAH ALIYAH FOR INCREASED COMMUNITY PARTICIPATION - Mohamad Erihadiana; Reza Fauzi; Juliani Jamilah (Balai Diklat Keagamaan Bandung, 2023)
Public relations is the most essential aspect of enhancing and maintaining the Institution's image. Ineffective implementation of public relations programs is frequently the cause of insufficient community participation. Therefore, it is necessary to analyze the sustainability of public relations initiatives in educational institutions through their management. This study was conducted at Madrasah Aliyah Sirnamiskin in the city of Bandung. This study aims to determine and analyze the management of public relations programs in Madrasah Aliyah Sirnamiskin Bandung City in an effort to increase community participation and the arrangement of an ideal madrasah environment. This study employs a qualitative research methodology with a descriptive technique of analysis. Annual programs, semester programs, quarterly programs, monthly programs, and weekly programs are the types of implementation of public relations programs that support increased community participation. In Madrasah Aliyah Sirnamiskin Bandung City, effective management in the preparation of public relations programs has implications for increasing community participation and constructing a positive madrasah environment.Keywords: Public Relations; Program; Participation; Society; Management